2020
DOI: 10.1177/2055102919898611
|View full text |Cite
|
Sign up to set email alerts
|

First-time mothers’ perceptions of social support: Recommendations for best practice

Abstract: Research indicates social support is imperative for postpartum well-being. The types of social support and access to preferred supports are less understood. This article considers first-time mothers’ perceptions of the effectiveness of social supports and perceived barriers to accessing support and provides recommendations for best practice. A search of the literature for terms related to postpartum social support was conducted. Major themes were identified and synthesised. A critique and analysis of the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 54 publications
3
43
0
10
Order By: Relevance
“…Some mothers in this study had some apparent structural support but did not see their partner, family or friends as safe and useful sources of functional support, particularly if they were ashamed of their situation or feelings, or were worried about the consequences of being perceived as not coping [41]. This is in line with the personal and social barriers to mobilizing postnatal social support identified by Negron et al [51] and De Sousa Machado et al [52], who note that there may be cultural differences in these barriers. Although the level of training varied between the projects [40], all the volunteers were trained in nonjudgemental active listening, confidentiality, non-directive information-giving and a strengths-based approach to building up mothers' confidence and self-efficacy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Some mothers in this study had some apparent structural support but did not see their partner, family or friends as safe and useful sources of functional support, particularly if they were ashamed of their situation or feelings, or were worried about the consequences of being perceived as not coping [41]. This is in line with the personal and social barriers to mobilizing postnatal social support identified by Negron et al [51] and De Sousa Machado et al [52], who note that there may be cultural differences in these barriers. Although the level of training varied between the projects [40], all the volunteers were trained in nonjudgemental active listening, confidentiality, non-directive information-giving and a strengths-based approach to building up mothers' confidence and self-efficacy.…”
Section: Discussionsupporting
confidence: 71%
“…[ 51 ] and De Sousa Machado et al . [ 52 ], who note that there may be cultural differences in these barriers. Although the level of training varied between the projects [ 40 ], all the volunteers were trained in non-judgemental active listening, confidentiality, non-directive information-giving and a strengths-based approach to building up mothers’ confidence and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 63 It has been observed that pregnant women and providers usually show an additional focus on birth rather than the postpartum period, given that this period is too far removed to be of immediate concern. 6 Researchers have reported that the effectiveness of social support depends on the relationship between support givers and receivers, 64 and thus ensuring an open and safe environment for sharing the experiences of emotional distress is imperative for connectedness and well-being. The inability of women to express feelings comfortably with health care providers may result from the fear of being perceived as a “bad mother” or as negligent, which may inhibit help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, an increase in conflicts and less commitment in the case of early-stage mothers may result from the overload of roles which they try to cope with. In some relationships, the woman is receiving little support from her partner, which leads to dissatisfaction with the relationship and can also be a source of conflicts and even mental problems [ 6 , 49 , 50 , 51 ]. The hypothesis that experiencing infertility could in some cases bring about positive outcomes was supported by studies conducted in Iran.…”
Section: Discussionmentioning
confidence: 99%